2012
DOI: 10.2141/jpsa.011031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inclusion of Probiotic, Prebiotic and Butyric Acid Glycerides on Resistance against Coccidiosis in Broiler Chickens

Abstract: This research was conducted to investigate the effects of single or combined use of probiotic (Primalac), prebiotic (Fermacto) and butyric acid glycerides (Baby C4) compared to salinomycin on resistance against coccidiosis in broiler chickens challenged with Eimeria. One day-old male Ross 308 broiler chicks were divided into 9 cages with 15 birds per each. Birds of different treatments received a regular corn-soybean meal basal diet supplemented with feed additives; none of them in negative control (C − ), sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 25 publications
10
29
1
Order By: Relevance
“…Mansoub (2011) reported that dietary sodium butyrate increased the weight gain and FCR up to 28 days of age. (Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Similarly, butyric acid enhanced the weight gain and FCR (Panda et al, 2009).…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 91%
See 1 more Smart Citation
“…Mansoub (2011) reported that dietary sodium butyrate increased the weight gain and FCR up to 28 days of age. (Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Similarly, butyric acid enhanced the weight gain and FCR (Panda et al, 2009).…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 91%
“…Beneficial health effects of butyrate or butyric acid are well documented, and it has been shown to have positive effects on broiler production parameters such as weight gain, feed intake, and FCR (Antongiovanni et al, 2007;Leeson et al, 2005;Taherpour et al, 2009). Chamba et al (2014) reported that partially coated sodium butyrate in broiler diet significantly increased the feed intake and weight gain, and improved FCR as compared to positive and negative controls during grower and finisher phases but not in the starter phase.…”
Section: Dissociation and Absorption Of Butyric Acidmentioning
confidence: 99%
“…Deconjugated bile acids are less soluble, hence less absorbed in the intestine and are more likely to excrete cholesterol and its fractionin faeces (Klaver and Van der meer, 1993) thus reduction of cholesterol accretion in the body. Previous work done by Taherpour et al (2009), Jang (2011), Mansoub (2011a, Kamal and Ragaa (2014) and Deepa et al (2017) showed reduced levels of serum total and LDL cholesterol without affecting HDL cholesterol level due to addition of various forms of BA. Similarly, serum triglyceride level was also found to be reduced when BAG was supplemented in broiler ration at 0.2 ( Jang, 2011;Mansoub, 2011a) and BA at 0.25 % (Dehghani-Tafti and Jahanian, 2016).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 87%
“…demonstrated similar results, with reduction in the total cholesterol and low density lipoprotein (LDL) cholesterol levels (Kalavathy et al, 2003;Taherpour et al, 2009) and triglycerides (Kalavathy et al 2003) in blood serum of broilers.…”
Section: Carcass Quality and Blood Parametersmentioning
confidence: 59%